Factors influencing sexual behaviors among Thai adolescents - Sitanan Srijaiwong (2017)
This cross-sectional analysis examines the factors influencing sexual behaviors, no-sex experience, safe sexual behaviors and unsafe sexual behaviors among adolescents, and the degree of sexual risk behaviors among sexually experienced adolescents by using web-based questionnaires. The participants were 3,192 Thai adolescents ages 15-19 and studying at secondary and vocational schools. Data were analyzed by using multinomial logistic regression analysis and multilevel regression analysis. Among all participants, 769 adolescents reported having had sexual experience defined as sexual intercourse (prevalence=24.09). Unsafe sexual behaviors escalated with age, enrollment in vocational school, greater perceived peer approval and sexual double standards. Unsafe sexual behaviors decreased with male gender, living with both parents having a higher sexual risk behavioral attitude and sexual message communication. The results revealed that school type was the greatest predictor influencing sexual risk behaviors followed by peer approval and sexual behaviors, type of family structure, living arrangements, sex, age, sexual risk behavioral attitude, sexual double standards and sexual message communication. In today’s society, external environmental factors have greater influence on sexual risk behaviors, especially school environment. And each adolescent has different contexts related to sexual behaviors. Hence, we should consider differences in individual, family and school contexts when developing an effective health system that promotes sexual health and sexual risk behavior prevention among adolescents, one that will lead to decreased negative outcomes from sexual behaviors among adolescents.